ANALISIS HUBUNGAN GAYA HIDUP DAN PERILAKU KONSUMSTIF IMPULSE BUYING DITINJAU DARI EKONOMI SYARIAH - Fadhilah Sukur Indra; namira muthia (J-EBI: Jurnal Ekonomi Bisnis Islam, 2022)
Islamic economics strongly carries the concept of al-falah as a welfare which is the ultimate goal of every living being, so with this transaction carried out in meeting their needs must also be based on this. However, this modern era has brought many social changes for all human beings, one of which is the emergence of a new lifestyle, namely hedonism and which is thought to be one of the factors that influence people to make impulse buying. This study aims to see the relationship of the hedonistic lifestyle to humans so that they are able to do impulse buying and how the Islamic economy responds to this. The method used is library research using several journal references. The results of the study that there is a relationship between the hedonism lifestyle with consumptive behavior of impulse buying and even Islamic economics clearly oppose this happening continuously because it deviates from the teachings of Islam itself.Keywords: Lifestyle, Hedonism, Impulse Buying, Islamic Economics.